STRENGTHENING THE GOVERNANCE OF CREATIVE TOURISM POTENTIAL BASED ON LOCAL WISDOM IN DAYU VILLAGE, GONDANGREJO DISTRICT, KARANGANYAR REGENCY, CENTRAL JAVA - Yohanes Martono Widagdo; Anita Andriantini Mulia (Fakultas Pariwisata Universitas Pancasila, 2022)
Strengthening the potential of creative tourism based on local wisdom as a form and alternative step in fostering the development of tourism potential and the creativity of tourism actors and communities around the tourist area. One of them is the Dayu tourist village area, because of the tourism potential it has. However, it tends to be managed as it is, and there is no synergy between tourist actors. The purpose of this research activity is to explore strengthening the governance of creative tourism potential in the Dayu tourism village area, Gondangrejo District, Karanganyar Regency, Central Java. This research uses qualitative descriptive methods in exploring the facts and conditions of local wisdom through self-help mapping and focus group discussions. The results of this research activity show that there is synergy between tourism actors and strengthening UMKM through Business Matching between buyers and tourism actors / the community, which is able to contribute to the sustainable improvement of the community's economy. Through efforts to strengthen various tourism potentials, making the tourist area increasingly fulfilled facilities and infrastructure, both in terms of natural tourism potential and local wisdom products produced by local residents towards the development of sustainable tourism villages.